Cover Image. (15th January 2020) - Hardin, Anna M.; Valiathan, Manish; Oh, Heesoo; Knigge, Ryan P.; McNulty, Kieran P.; Leary, Emily V.; Duren, Dana L.; Sherwood, Richard J.
Abstract : The cover image is based on the Original Article Clinical implications of age‐related change of the mandibular plane angle by Anna M. Hardin et al., https://doi.org/10.1111/ocr.12342 .